Simultaneous saccharification and ethanologenic fermentation (SSF) of waste bread by an amylolytic Parageobacillus thermoglucosidasius strain TM333 - Christopher C. Ibenegbu; David J. Leak (Microbial Cell Factories, 2022)
Abstract The starch in waste bread (WB) from industrial sandwich production was directly converted to ethanol by an amylolytic, ethanologenic thermophile (Parageobacillus thermoglucosidasius strain TM333) under 5 different simultaneous saccharification and fermentation (SSF) regimes. Crude α-amylase from TM333 was used alone or in the presence of amyloglucosidase (AMG), a starch monomerizing enzyme used in industry, with/without prior gelatinisation/liquefaction treatments and P. thermoglucosidasius TM333 fermentation compared with Saccharomyces cerevisiae as a control. Results suggest that TM333 can ferment WB using SSF with yields of 94–100% of theoretical (based on all sugars in WB) in 48 h without the need for AMG addition or any form of heat pre-treatment. This indicates that TM333 can transport and ferment all of the malto-oligosaccharides generated by its α-amylase. In the yeast control experiments, addition of AMG together with the crude α-amylase was necessary for full fermentation over the same time period. This suggests that industrial fermentation of WB starch to bio-ethanol or other products using an enhanced amylolytic P. thermoglucosidasius strain could offer significant cost savings compared to alternatives requiring enzyme supplementation.